MENAKAR PENGGUNAAN RUMAH TAHANAN MILIK TENTARA NASIONAL INDONESIA OLEH KOMISI PEMBERANTASAN KORUPSI DALAM PERSPEKTIF HUKUM ADMINISTRASI NEGARA - Muchamad Arif Agung Nugroho (Fakultas Hukum Universitas Wahid Hasyim, 2012)
Now days, KPK (Anti-Corruption Commission) is cooperating with TNI (Indonesian National Army) for borrowing Kodam Jaya’s detention facilities. That policy makes problem, so this papper answers the problem in administrative law perspective. After studied legislation, researcher found violation of human right because KPK is not author to make detention facilities. KPK have violated AAUPB (principles of good governance). Next time, KPK must cooperate with Kemenkumham (Ministry of Law and Human Rights) who are real author to make detention facilities.